Experimental Lachesis muta rhombeata envenomation and effects of soursop (Annona muricata) as natural antivenom. Issue 1 (December 2016) - Cremonez, Caroline; Leite, Flávia; Bordon, Karla; Cerni, Felipe; Cardoso, Iara; Gregório, Zita; de Souza, Rodrigo; de Souza, Ana; Arantes, Eliane
Abstract Background In the Atlantic forest of the North and Northeast regions of Brazil, local population often uses the fruit juice and the aqueous extract of leaves of soursop (Annona muricata L.) to treatLachesis muta rhombeata envenomation. Envenomation is a relevant health issue in these areas, especially due to its severity and because the production and distribution of antivenom is limited in these regions. The aim of the present study was to evaluate the relevance of the use of soursop leaf extract and its juice against envenomation byLachesis muta rhombeata . Methods We evaluated the biochemical, hematological and hemostatic parameters, the blood pressure, the inflammation process and the lethality induced byLachesis muta rhombeata snake venom. We also assessed the action of the aqueous extract of leaves (AmL) and juice (AmJ) fromA. muricata on the animal organism injected withL. m. rhombeata venom (LmrV) in the laboratory environment. Results LmrV induced a decrease of total protein, albumin and glucose; and increase of creatine kinase, aspartate aminotransferase, and urea concentrations. It provoked hemoconcentration followed by reduction of hematocrit, an increase in prothrombin time and partial thromboplastin time and a decrease of the blood pressure. LmrV induced the release of interleukin-6, an increase in neutrophils and changes in the serum protein profile, characteristic of the acute inflammatory process. LD50 values were similar for the groups injected with LmrV and treated or untreated with AmJ and AmL. Both treatments play a role on the maintenance of blood glucose, urea and coagulation parameters and exert a protective action against the myotoxicity. However, they seem to worsen the hypotension caused by LmrV. Conclusion The treatments with AmJ and AmL present some beneficial actions, but they might intensify some effects of the venom. Therefore, additional studies onA. muricata are necessary to enable its use as natural antivenom for bushmaster snakebite.